Interrelation among one-carbon metabolic (OCM) pathway-related indicators and its impact on the occurence of pregnancy-induced hypertension disease in pregnant women supplemented with folate and vitamin B12: Real-world data analysis - Zhang, Yanfei; Gu, Chenhong; Lei, Ying; Wang, Jingwen; Sun, Leiqin; Fan, Junwei; Wang, Yanlin; Zhang, Xiaoqing (Frontiers in Nutrition, 2023)
Background and objective: A considerable number of pregnant women were supplemented with folate and vitamin B12, major participants of the one-carbon metabolic (OCM) pathway. The aim of our study was to explore the effects of OCM related indicators on PIH and PE in pregnant women with folate and vitamin B12 supplementation. Subjects and Methods: 1178 pregnant women who took multivitamin tablets containing 800μg folate and 4μg vitamin B12 daily from 3 months before pregnancy to 3 months after pregnancy were enrolled in this study. These pregnant women were classified into three groups: normotensive group (n=1006), PIH group (n=131), and PE group (n=41). The information of age, weight, body mass index (BMI), number of embryos, gravidity, parity, and OCM related indicators (serum level of homocysteine, folate, and vitamin B12; MTHFR C677T genotype) was collected. Results: The accuracy of prediction model based on the screened independent risk factors (hyperhomocysteine, OR=1.170, 95%CI=1.061-1.291; high folate status, OR=1.018, 95%CI=0.999-1.038; and high BMI, OR=1.216, 95% CI=1.140-1.297) for PIH in subjects with MTHFR CC genotype (AUC=0.802) was obviously higher than that in subjects with MTHFR CT，TT genotype (AUC=0.684，0.685 respectively) by receiver operating characteristic curve analysis. Homocysteine level of PIH group was significantly higher than that of normotensive group only in subjects with MTHFR CC genotype (p=0.005). Negative correlation between homocysteine and folate appeared in subjects with MTHFR CT+TT genotype (p=0.005). A model including multiple embryos, nulliparas, and lower folate could predict the process from PIH to PE（AUC=0.781, p<0.0001）. Conclusion: The prediction model composed of homocysteine, folate and BMI for PIH was suitable for subjects with MTHFR CC genotype in pregnant women with supplemention of folate and vitamin B12. Lower folate level could be an independent risk factor in developing process from PIH to PE.